A facile synthesis of Cs loaded TiO2 nanotube photoelectrode for the removal of 4-chloroguaiacol. (March 2019) - Rajput, Himadri; Changotra, Rahil; Sangal, Vikas Kumar; Mahla, Sunil Kumar; Dhir, Amit
Abstract: In this study, novel Cesium (Cs) doped TiO2 nanotubes photoelectrode (Cs/TiO2 NTs) were synthesized by simple electrochemical anodization method and characterized by several physicochemical techniques. In particular, the photocatalytic (PC), electrocatalytic (EC) and photoelectrocatalytic (PEC) activity of newly synthesized Cs/TiO2 NTs electrodes was investigated using 4-Chloroguaiacol (4-CG). The effect of operating parameters like Cs concentration, electrolyte concentration, external current and pH on degradation efficacy was examined. PEC oxidation using Cs/TiO2 NTs lead to 92% degradation of 4-CG in 6 h of solar light irradiation under optimized conditions (2.5 mM Cs, 160 mg L −1 Na2 SO4, 0.03 A current and pH 3). A comparative assessment between PEC, PC and EC process manifested that PEC process was most efficient than the other two processes and Cs/TiO2 NTs exhibited higher PEC activity than bare-TiO2 electrodes in terms of degradation and mineralization of organic pollutant. The generation of OH radicals was found to be highest in PEC when compared to EC and PC process. Possible intermediates/byproducts were identified by GC-MS technique and a corresponding tentative degradation pathway has been proposed. Cytotoxicity study showed that PEC has potential to detoxify 4-CG. Hence, combination of TiO2 electrodes decorated with Cs metal can act as a highly efficient photoelectrode for the degradation of hazardous pollutants. Graphical abstract: Image 1 Highlights: Novel Cs/TiO2 NTs electrode fabrication by anodization for PEC removal of 4-CG. Comparative assessment of photocatalysis, electrocatalysis and photoelectrocatalysis performances. Photoelectrocatalytic process was most efficient in terms of % removal, TOC reduction and OH generation. Identification of degradation intermediates and cytotoxicity assessment.